Immature Platelet Fraction and Acute Coronary Syndrome; a Systematic Review and Meta-Analysis - Jafari Afshar, Elmira; Shahnavaz, Vahid; Talakoob, Hamed; Kafialqora, Parnaz; Madady, Aryan; Pourbahrighesmat, Shamimeh; Tayebi , Amirhossein; MozafaryBazargany , Mohammadhossein; Gholami , Niloofar; Ayati , Aryan; et al. (Archives of Academic Emergency Medicine, 2024)
Introduction: Immature Platelet Fraction (IPF) is a measure of the proportion of reticulated platelets (RPs) to all platelets in circulation. IPF may have both prognostic and diagnostic values in patients with Acute Coronary Syndrome (ACS). This study aims to comprehensively summarize the diagnostic utility of IPF levels in patients with ACS, specifically focusing on its ability to differentiate between different subtypes of ACS. Methods: We conducted a systematic search in online databases including MEDLINE, Scopus, and Google Scholar up to March 4th 2024, to identify relevant studies. The random-effect model, employing inverse variance for mean differences (MD) and Mantel-Haenszel methods for odds ratios (OR) were utilized to combine the data. Joanna Briggs Institute (JBI) appraisal tool was employed to assess the quality of included studies. Results: Our systematic review contains 15 articles with a total sample size of 2,030 ACS patients. Pooled analysis revealed significant differences in IPF levels of ACS patients compared to healthy controls (MD (95%CI): 2.85 (0.86, 4.85), P-value = 0.004) and stable angina patients (MD (95%CI): 0.58 (0.23, 0.92), P-value < 0.001). Subgroup comparisons within ACS patients demonstrated higher IPF levels in myocardial infarction (MI) vs. unstable angina (UA) (MD (95%CI): 1.81 (0.41, 3.22), P-value = 0.01), ST elevation MI (STEMI) vs. non-ST elevation (NSTEMI) ACS (MD (95%CI): 0.74 (0.31, 1.17), P-value < 0.001), and NSTEMI vs. UA (MD (95% CI): 1.07 (0.24, 1.90), P-value = 0.01). Conclusion: IPF levels could increase in patients with ACS, particularly during the acute phase of STEMI. This suggests that IPF may be a useful biomarker for early diagnosis of ACS. Additionally, IPF levels may help differentiate between ACS subtypes.